Arduino Based Temperature And Humidity Monitoring Control System for Day Old Chicken (DOC) Cage - Sujiwa, Akbar; Ubaydillah, Muhammad (BEST, 2021)
In general, conventional cattle sheds using manual systems and human labor are very reliable, in the conventional process of heating cattle sheds, we still encounter many using oil stoves and lamps as a DOC heating process. However, the use of oil stoves and lamps is dangerous and unstable. In addition to the DOC heater using the lamp, there is also a DOC heater using an element heater. The advantage of using a heating element, the temperature can be adjusted according to your needs. The use of heating elements in chicken coops is still rarely used. Therefore, a research was conducted on the manufacture of a temperature and humidity monitoring control system based on Arduino Mega in the Day Old Chicken (doc) cage. DHT 11 sensor accuracy level calibrated with room temperature measuring instrument Taffware HTC-2 is known DHT 11 sensor has an accuracy in reading temperature that is 96% with a dispute of 3.8%. And the accuracy in reading humidity is 89.8% with a difference of 11%.